Diverfication and value addition (UN New YorkUS, 2018)
Outlines the challenges faced by commodity-dependent countries that are vulnerable to volatile commodity export prices. Discusses the reasons why commodity dependence can have negative effects on growth and development in a country and identifies which individual commodities and commodity groups display the most volatile prices.
Note by the UNCTAD Secretariat.